(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and paraclinical characteristics and to evaluate the association of these features with the response to Tyrosine Kinase Inhibitors (TKI) in non-small cell lung cancer patients with EGFR gene mutation at 19-8 Hospital. Patients and methods: A clinical intervention, cross-sectional descriptive study, combining retrospective and prospective analysis without a control group, was conducted on 30 patients with stage IV EGFR-mutant non-small cell lung cancer receiving first-line TKI therapy from January 2022 to November 2024. Results: The mean age was 62.2 ± 13.3 years; the male-to-female ratio was 2:1. Patients with an ECOG performance status of 0-1 accounted for the vast majority (96.6%), with no recorded cases of ECOG = 3. Single-site/organ metastasis was the most common presentation (46.7%), while EGFR gene mutation on exon 19 were more frequent (63.3%). Although no statistically significant difference was found between treatment response rates and clinical, paraclinical factors, or TKI types (p > 0.05), Osimertinib showed the best response (100%), and exon 19 mutations responded better than exon 21 mutations (84.2% vs. 54.5%). Conclusion: The study found no statistically significant correlation between clinical or paraclinical factors and TKI treatment response in patients with stage IV EGFR-mutant non-small cell lung cancer.